2018
DOI: 10.1002/2018gl077382
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of the Glacial‐Interglacial Methane Increase Constrained by Stable Isotopes and Earth System Modeling

Abstract: The observed rise in atmospheric methane (CH 4 ) from 375 ppbv during the Last Glacial Maximum (LGM: 21,000 years ago) to 680 ppbv during the late preindustrial era is not well understood. Atmospheric chemistry considerations implicate an increase in CH 4 sources, but process‐based estimates fail to reproduce the required amplitude. CH 4 stable isotopes provide complementary information that can help constrain the underlying causes of the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…CH 4 emissions are a function of microbial activity, i.e., temperature, available substrate, and wetland area (63). Total preindustrial emissions are scaled to 140 TgCH 4 /y for each model, consistent with the observed methane isotope and concentration measurements (64).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…CH 4 emissions are a function of microbial activity, i.e., temperature, available substrate, and wetland area (63). Total preindustrial emissions are scaled to 140 TgCH 4 /y for each model, consistent with the observed methane isotope and concentration measurements (64).…”
Section: Methodsmentioning
confidence: 86%
“…We combine the CH 4 source estimates with the lifetime calculation in a global mean budget calculation B = S × τ , where B is the atmospheric CH 4 burden in Tg, S is the global mean CH 4 source, and τ is the lifetime in years (64). The budget equation is combined with the parametric lifetime model and the soil uptake, which is multiplied by the resultant concentration divided by preindustrial value.…”
Section: Methodsmentioning
confidence: 99%
“…Our ability to reproduce the observed latitudinal distribution of δ 13 C depends not only on the assumed value of global mean Cl, but also its geographic distribution. The detailed halogen chemistry model (TOMCAT) of Hossaini et al (2016) places the maximum Cl values in the continental NH, in contrast to the large MBL Cl sink used in Allan et al (2007) to explain SH observations. We find that the strong NH Cl maximum, along with the resulting reduction in OH fractionation required to maintain consistency with observations, acts to flatten the interhemispheric gradient of δ 13 C, while the MBL Cl sink increases the hemispheric differences in NH winter and also strengthens the seasonal cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Both SimStd and SimGC are thus below the 1 % loss via Cl suggested by Gromov et al (2018). We conduct a third sensitivity simulation, SimTom, which uses Cl from the TOMCAT model simulations that include chlorine sources from chlorocarbons (including very short lived substances), HCl from industry and biomass burning, and very short lived substances (Hossaini et al, 2016). This simulation leads to Cl accounting for 2.5 % of tropospheric CH 4 loss in our simulation.…”
Section: Description Of Simulationsmentioning
confidence: 99%
See 1 more Smart Citation